Teaching of the subject ‘Biomolecules in Living Organisms’ using 3D printing models - Gul, Seyda; Yalinkilic, Funda (Education and information technologies, 2025)
In recent years, 3D printing technology or 3D printing models have become a powerful educational tool used in many fields such as medicine, engineering and science. However, research on the integration of these technologies into formal educational environments and the researches examining their effect on students’ learning biology is quite limited. The aim of this study is to examine the effect of using 3D printing models on students’ learning the subject ‘Biomolecules in Living Organisms’. In the study, the students were also interviewed, and the usefulness of 3D printing models was evaluated. For this aim, a quasi-experimental design was used in the study. The study group consisted of 61 ninth grade students (37 females, 24 males), 32 students in the control group and 29 students in the experimental group, attending a public high school during the academic year 2023–2024. The findings indicated that the achievement levels of the students in the experimental group (3D printing models) were statistically higher than those in the control groups (non-3D printing models) after a 9-week instruction. The findings also indicated that there is a statistically important difference in students’ scores on retention tests in favour of the experimental group. Similarly, as a result of student interviews, it was determined that 3D models were evaluated by most of the students as materials that were interesting, arousing curiosity, increased the memorability of information, concretized the subject and facilitated learning. Despite these positive effects of 3D printing models on learning, some limitations, such as small sample selection, reduced the generalizability of the study results. Considering these limitations, some suggestions for future research were made.